Inoculating a New Generation: Immunology in Medical Education - Haidaris, Constantine G.; Frelinger, John G. (Frontiers in Immunology, 2019)
Educating the next generation of physicians is a key means of communicating and disseminating impactful immunologic scientific knowledge, and its practical application to human disease. We present our perspective, using as our model a first-year medical school course entitled Host Defense. As the name suggests, immunology is the overarching principle that links the multiple subjects in the course. We address a range of immunologically relevant topics, including innate and adaptive immunity, vaccines, inflammation, allergy, tumor immunotherapy, transplantation, and autoimmunity. These topics are integrated with the fields of infectious diseases, pathology, clinical laboratory testing and public health, to illustrate how the basic science discoveries in immunology are relevant to clinical practice. The course objectives are not only to deliver “first principles” and molecular mechanisms, but also to connect these principles with the clinical world of diagnosis and therapy. We detail the different methodologies used to achieve these objectives and to reach today’s medical students. This provides a framework for course structure and execution designed to engage both the novice and the more “immunologically experienced” learner. The framework includes classical didactic components and personalized instructor access, aligned with current approaches to self-directed learning and using digital media.  We also address some of the challenges of assembling a course like Host Defense in the context of an academic medical center with multiple scientific, educational, and clinical missions. This perspective is not meant be proscriptive, but rather to outline our experiences on the strategies tried, while describing their advantages and drawbacks in teaching immunology.